PERAN ORANG TUA PADA PEMBELAJARAN DALAM JARINGAN (DARING) DI MASA PANDEMI COVID-19 DI DESA BANGSAL KECAMATAN PESANTREN KOTA KEDIRI - Amida Nur Hidayanti; Listyaningsih Listyaningsih (Universitas Negeri Surabaya (Unesa), 2022)
Abstract This study aims to describe the role of parents in online learning during the Covid 19 pandemic in Bangsal village Pesantren district Kediri city. The theory used in this research is the Biddle & Thomas theory . The research approach used in this research is a qualitative approach with a descriptive type of research. Data collection was done by interview, observation, and documentation. The results of this study explain that the role of parents ia s guide, educator, carer, developer, and supervasior. During the online learning period so far, parents in the Bangsal village Pesantren district Kediri city always try to provide the best assistance for children in the learning process. Assistance provided by parents as well as preparing the completeness for the online learning process that will be carried out and being willing to accompany children when online learning takes place. Parents want that even though learning is done online, children can follow the learning to the maximum and remain enthusiastic in undergoing education. Parents play an importantrole in the progress of childrens learning because from thr encouragement of parents, children can regenerate their childrens learning spirit. Parents in the Bangsal village Pesantren subdistrict Kediri city explained the they always accompany their children when learning takes place and prioritize the interests of their children rather than their busy lives. Keywords: content, formatting, article